System Theory, Proton Stability, Double-Slit Experiment, and Cyclotron Physics - Sorli, Amrit Srecko (JOURNAL OF ADVANCES IN PHYSICS, 2020)
Every system is composed of constitutional elements that are stable. Unstable elements cannot build a system. The hydrogen atom, for example, is the system composed out of two stable elements: proton and electron. How proton could be a system made out of unstable elements as quarks and gluons is an unanswered question that particle physics need to face in order to strengthen its theoretical basis. System Theory offers an original interpretation of double-slit experiment and requires re-examination of cyclotron physics.